2020
DOI: 10.3126/jpahs.v7i1.28860
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of COVID-19 and perception of work satisfaction among healthcare workers at Patan Hospital, Nepal

Abstract: Introduction: Healthcare workers (HCWs) awareness of disease outbreak, and working efficiently in a changed environment is vital to fight pandemic. How an institution responds to the crisis depends on HCWs response. This study aims to find out awareness of COVID-19 and work satisfaction of HCWs at Patan Hospital (PH), Nepal. Method: A cross-sectional questionnaires base descriptive study was conducted at PH, Patan Academy of Health Sciences, Nepal, in April 2020. The HCWs were grouped in to technical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…A written form of questionnaire was designed which consisted of questions assessing demographics, knowledge, attitude and practice towards COVID-19. These prevalidated questions were compiled from three studies conducted in Iran 5 Pakistan 7 and in Nepal 8 and were derived from the 'World Health Organization COVID-19 facts and myth busters' 9 .…”
Section: Methodsmentioning
confidence: 99%
“…A written form of questionnaire was designed which consisted of questions assessing demographics, knowledge, attitude and practice towards COVID-19. These prevalidated questions were compiled from three studies conducted in Iran 5 Pakistan 7 and in Nepal 8 and were derived from the 'World Health Organization COVID-19 facts and myth busters' 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, being a public hospital there were no economic burden placed to the staffs. 20 Whereas, the study done among nurses in Philippines demonstrated moderate level of perceived social and organizational support. 21 Several studies have clearly demonstrated that increased organizational and social support were directly associated with increased personal life satisfaction, resilience and decreased psychological problems such as job stress and anxiety related to COVID-19.…”
Section: Resultsmentioning
confidence: 94%
“…19 In contrast to these findings, the study from one of the tertiary centers from Nepal showed that health care workers were aware of COVID-19 and were satisfied to their work. 20 The difference on the findings may be because of the different set up of the institution, which is one of the leading public medical colleges that has a very good infection control measures and till that time no health care workers were reported to be infected with COVID-19 in Nepal. Moreover, being a public hospital there were no economic burden placed to the staffs.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, they became more professional and experienced more professional satisfaction, team work and altruism in this period, and they realized once again what a sacred duty intensive care nurses perform. In a study conducted in Nepal, technical personnel (nurses, laboratory and radiology technicians) and doctors were found to have high job satisfaction levels during the COVID-19 period (Acharya et al, 2020). Liu et al (2020), Sethi et al (2020) and Sun et al (2020) stated in their studies that lifesaving was also a responsibility of nursing, nurses were proud of their career choices, further gained their professional identities and strength in this period, could overcome every duty, experienced team spirit and continuously supported each other.…”
Section: Discussionmentioning
confidence: 99%